Peran Penting Bimbingan dan Konseling dalam Menangani Tantangan Pernikahan Dini: Strategi untuk Membangun Hubungan yang Sehat - Hidayah, Nor; Billah, Chasnah Mustakfi; Hayati, Sri Ayatina; Kushendar, Kushendar (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
Marriage is considered the basis for carrying out better social engineering and is one of society's most important basic principles of life. Quality family building is considered to foster a superior generation for a nation. However, happiness in marriage is not always easy to achieve, sometimes, the partner's expectations do not match the reality of domestic life. The inability of a prospective bride and groom to prepare provisions to build family resilience can cause various problems. Early marriage, which occurs among teenagers under the age of 20, is still a phenomenon in Indonesia. Factors such as economics, parental influence, and local community customs contribute to the practice of early marriage. Couples who marry at a young age often face problems due to a lack of maturity in managing communication, conflict and emotions. Pre-marital guidance is considered an effort to overcome a couple's inability to build family resilience. Marriage counseling is a necessary solution for families experiencing disharmony, intending to minimize problems and achieve happiness in married life. Marriage counselors, as trained professionals, aim to help couples resolve their marital problems. Marriage counseling aims to help couples understand and accept their differences, create good relationship patterns, and resolve conflicts. This literature study concludes that early marriage can cause various problems, and marriage counseling has an important role in overcoming these conflicts. Counseling helps couples understand, accept, and resolve their differences, minimize problems, and achieve happiness in marriage.